THE RIGHT TO INHERIT CHILDREN IN MIXED MARRIAGES BETWEEN BALINESE AND FOREIGN NATIONALS - I Nyoman Wahyu Ariartha; I Gede Agus Kurniawan (Warmadewa Press, 2023)
Currently, the province of Bali does not rule out the possibility of inter-citizenship marriages, in this case between Balinese Indonesian citizens and foreigners raise doubts about the inheritance rights of children born from this mixed marriage, whether inheriting from the father's family or from the mother's family. The importance of legal certainty about children's inheritance rights is due to problems that occur. It is important to examine the position of children born from mixed marriages in the field of inheritance, considering the absence of special arrangements regarding inheritance in mixed marriages. This study aims to examine the citizenship and inheritance rights of children from Balinese-foreign national mixed marriages. This study employs normative legal research with a statutory and conceptual approach. It utilizes primary, secondary, and tertiary legal materials collected through a card system technique and employs evaluative, systematic, interpretative, and argumentative analysis methods. The result of the study revealed that the citizenship status of a child who is from a mixed marriage is determined in Article 4 and Article 6 of the Citizenship Law of a child born from a mixed marriage, between Balinese Indonesian citizens and foreigners, status as Indonesian citizens. Only in the event that the nationality obtained from the marriage of the parents causes the child to have dual citizenship, then the child must choose his nationality when the child is 18 years old or married. The inheritance rights of children born from mixed marriages depend on the form of marriage of their parents.